Finnish based mutual funds performance in emerging equity markets - Koivisto, Jarno (My University, 2024)
This thesis examines the performance of Finnish-based mutual funds investing in emerging equity markets. The primary objective is to determine whether these funds generate risk-adjusted excess returns relative to benchmark indices during the period 2014–2023. A comprehensive review of financial literature provides the theoretical framework, focusing on key performance metrics such as Jensen's Alpha, the Modigliani-Modigliani risk-adjusted measure (M²), and Tracking Error. These tools are employed to evaluate seven Finnish mutual funds selected based on their relevance, data availability, and long-term track records. The empirical results indicate that Finnish mutual funds in emerging equity markets, on average, outperform their benchmarks on a risk-adjusted basis. Strong performance trends were particularly evident among funds managed by specialized asset management firms. The analysis of risk-adjusted returns and Tracking Error highlighted the success of active management strategies in navigating the complexities of emerging markets. These findings suggest that Finnish portfolio managers effectively leverage their expertise and disciplined investment approaches to achieve exceptional outcomes in challenging market environments. While the findings suggest robust performance, the study acknowledges limitations, including the small sample size and the relatively short time horizon. These factors may influence the generalizability of the results. This research challenges prevailing assumptions in the academic literature regarding the underperformance of actively managed funds. It highlights the potential of Finnish portfolio managers to achieve excess returns in emerging markets, driven by disciplined, long-term, and conservative investment strategies.

Tämä tutkielma tarkastelee suomalaisten sijoitusrahastojen performointia kehittyvillä osakemarkkinoilla. Tutkimuksen päätavoitteena on selvittää, tuottavatko nämä rahastot riskikorjattuja ylituottoja suhteessa vertailuindekseihin vuosien 2014–2023 aikana. Kirjallisuuteen perustuva kattava teoriaosuus muodostaa tutkielman teoreettisen viitekehyksen ja keskittyy keskeisiin tuottomittareihin, kuten Jensenin alfaan, Modigliani-Modigliani (M²) riskikorjattuihin mittareihin ja Tracking Error -analyysiin. Näitä mittareita hyödynnetään arvioitaessa seitsemää valittua suomalaista rahastoa, jotka on valittu niiden relevanttiuden, datan saatavuuden ja pitkän aikavälin tuottohistorian perusteella. Empiiriset tulokset osoittavat, että suomalaiset kehittyville markkinoille sijoittavat rahastot ylittävät keskimäärin vertailuindeksinsä riskikorjatulla tuotolla. Erityisen vahvoja tuottotrendejä havaittiin varainhoitoyhtiöiden hallinnoimissa rahastoissa. Riskikorjattujen tuottojen ja Tracking Error -mittarin analyysi korosti aktiivisen salkunhoidon strategioiden menestystä kehittyvien markkinoiden haasteiden hallinnassa. Tulokset viittaavat siihen, että suomalaiset salkunhoitajat hyödyntävät tehokkaasti asiantuntemustaan ja kurinalaisia sijoitusstrategioitaan saavuttaakseen poikkeuksellisia tuloksia haastavissa markkinaympäristöissä. Vaikka tulokset osoittavat vahvaa suorituskykyä, tutkimus tunnistaa myös rajoitteita, kuten pienen otoskoon ja suhteellisen lyhyen tarkastelu ajanjakson. Nämä tekijät voivat vaikuttaa tulosten yleistettävyyteen. Tutkimus haastaa akateemisessa kirjallisuudessa vallalla olevat oletukset aktiivisesti hallinnoitujen rahastojen alisuoriutumisesta. Tutkielma tuo esille suomalaisen salkunhoitajan potentiaalin saavuttaa ylituottoja kehittyvillä markkinoilla kurinalaisten, pitkäjänteisten ja konservatiivisten sijoitusstrategioiden avulla.
Keywords: Finnish, Mutual Fund, Emerging Markets, Portfolio Management, Risk-adjusted, Performance, Suomalainen, Sijoitusrahasto, Kehittyvät markkinat, Salkunhoito, Riski-korjattu, Tuotto